Target reliability analysis of bridge piers concerning the earthquake extreme event limit state. (15th October 2021) - Safari, Mohammad; Ghasemi, Seyed Hooman; Haj Seiyed Taghia, Seiyed Ali
Highlights: In this study, a new method is proposed to calculate the target reliability index of the bridge's piers associated with the extreme limit state function concerning seismic design criteria. As a-state-of the-art, the reliability index of bridge pier is stipulated using a new generation of the limit state function corresponding to the interaction. The objective function of the target reliability is updated to explicitly compromise the uncertainties of the seismic using the probabilistic seismic hazard analysis. The contour concept is provided to determine the target reliability analysis of the concrete bridge pier subjected to the earthquake extreme events. Abstract: Target reliability is an essential design constrain for probabilistic-based design approaches. The target reliability analysis requires a double optimization process concerning the trade-off between safety and cost. In this study, a new method is proposed to calculate the target reliability index of the bridge's piers associated with the extreme limit state function concerning seismic design criteria. First, as a-state-of the-art, the reliability index of bridge pier is stipulated using a new generation of the limit state function corresponding to the interaction failure mode. In doing so, a sophisticated reliability assessment is introduced to compute the reliability level of the pier subjected to the flexural and axial failure modes using a probabilistic interaction surface. In an attempt to capture more sustainable target reliability, an optimization approach is emphasized to minimize the structural cost function at a different structural lifetime. In addition, the objective function of the target reliability is updated to explicitly compromise the uncertainties of the seismic using the probabilistic seismic hazard analysis while the structural resistance probability model is driven using the Monte Carlo simulation. It should be noted that the structural maintenance and structural failure cost are modeled using the relationship between the initial cost and economic inflation rate corresponding to the expected lifetime. Subsequently, the contour concept is provided to determine the target reliability analysis of the concrete bridge pier subjected to the earthquake extreme events.